Trend vývoje upravené přidané hodnoty ve vybraných dopravních podnicích měst ČR - Šenec, Alexandr; Pazderková, Ivana (Univerzita Pardubice, 2013)
The article deals with the development of the value added per employee in a public transport. The value added is adjusted by the reimbursement for demonstrable loss from state, region or municipality that guarantee transport services on the particular areas. The economy of transport companies combines the basic business target - a profit - and the possibility of the financial support from state, region or municipality in a form of a reimbursement for demonstrable loss. The article analyzes the data about the biggest transport companies in the Czech Republic. The companies were viewed as a whole at first and then they were divided to three groups. The value added per employee allows comparing the companies, comparing the groups of companies and evaluation of the progress of value added in one company through the years. Desirable development is the growing trend in the value added per employee. The paper also analyzes the extent to which the reimbursement for demonstrable loss participates in the results. That is why the paper deals with the comparing of increase of the value added and of increase of the reimbursement for demonstrable loss. The article also includes general suggestions for management of transport companies to ensuring the increase of value added.
The development trend of adjusted value added in selected transport companies in the Czech Republic
Keywords: public transport; urban public transport; transport company; value added per employee; reimbursement for demonstrable loss